2016
DOI: 10.1111/bor.12212
|View full text |Cite
|
Sign up to set email alerts
|

Late Saalian and Weichselian glaciations in the German Baltic Sea documented by Pleistocene successions at the southeastern margin of the Arkona Basin

Abstract: Seismic profiles and numerous sediment cores of a planned offshore wind farm area northeast of Rügen Island provide a unique insight into the distribution and thickness of glacial deposits in the southern Baltic Sea. Fine gravel analysis enabled recognition of five tills that correspond to different ice advances. On the basis of a 3D structural model, the main Pleistocene events could be reconstructed and correlated with stratigraphical records in the circum‐Baltic area comprising Marine Isotope Stages (MIS) 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…At KKH, we find no evidence for an early-to mid-Weichselian SIS advance into the SW Baltic Sea, as previously proposed by M€ uller (2004a, b; 'Warnow advance'), Houmark-Nielsen (2010; 'Ristinge advance', Fig. 9), Stephan (2014; 'Ellund advance'), and more recently by Obst et al (2017). Although it is conceivable that the associated glacial deposits were removed (i.e.…”
Section: Broader Regional Contextsupporting
confidence: 66%
“…At KKH, we find no evidence for an early-to mid-Weichselian SIS advance into the SW Baltic Sea, as previously proposed by M€ uller (2004a, b; 'Warnow advance'), Houmark-Nielsen (2010; 'Ristinge advance', Fig. 9), Stephan (2014; 'Ellund advance'), and more recently by Obst et al (2017). Although it is conceivable that the associated glacial deposits were removed (i.e.…”
Section: Broader Regional Contextsupporting
confidence: 66%
“…Remnants of post‐Saalian interglacial sediments and Middle Weichselian tills were drilled at the southeastern margin of the Arkona Basin (Obst et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Obst et al . ). Exposures of marine or brackish‐marine and limnic deposits representing warmer periods of the Pleistocene, in part with ice‐free conditions, e.g.…”
mentioning
confidence: 97%
“…Hermsdorf and Strahl, 2008). The existence of an Early to Middle Weichselian ice advance (Warnow advance, Müller, 2004a, b;Obst et al, 2017) reaching MWP has so far not been incontestably confirmed (Kenzler et al, 2018). A possible correlation of this Warnow advance with the Danish Ristinge advance (56-46 ka) has been proposed by Houmark-Nielsen (2010).…”
Section: The Early To Middle Weichselian (115-27 Ka)mentioning
confidence: 99%